95.4k views
2 votes
Solve for M: -11E=2M

2 Answers

3 votes

Answer:

M = -(11 e)/2

Explanation:

Solve for M:

-11 e = 2 M

Hint: | Reverse the equality in -11 e = 2 M in order to isolate M to the left hand side.

-11 e = 2 M is equivalent to 2 M = -11 e:

2 M = -11 e

Hint: | Solve for M.

Divide both sides by 2:

Answer: M = -(11 e)/2

User Pinu
by
6.0k points
7 votes

Answer:


(-11E)/(2) = M

Explanation:

Divide each side by 2:


(-11E)/(2) = (2M)/(2)  \\\\frac{-11E}{2} = M

User Priidu Neemre
by
5.7k points